MAINTAINING THE HARMONY OF NATURE BEHIND THE EXISTENCE OF BATU BELAH MYTH IN KAMPONG TUA NONGSA - Tomi Arianto; Melly Siska Suryani (BASIS (Bahasa dan Sastra Inggris), 2020)
This study aimed to explore the harmonious relationship between human and nature that is still maintained by the Malay people of Kampong Tua Nongsa in Batam. Everyone who visited Batam will have perception that Batam is an industrial city with various metropolis conditions. It cannot be denied that it is true. The industrialization magnet in Batam has attracted the attention of many immigrants from various regions to try their luck to be better. The effects of rapid immigration and the many industrialization of Batam have had quite an impact on environmental conditions, especially this island which is bordering with Malaysia and Singapore. The amount of industrial pollution, deforestation, settlements, and reclamation has a bad impact on the natural situation. But behind all of that, Batam has uniqueness. The government still maintains there are 37 points of Kampong Tua Malay scattered throughout Batam. Behind the glamor of Batam's industrialization, there are still remnants of Malay culture that have a close relationship with the environment. In the research conducted, researchers analyzed three of cultural objects that are still preserved, namely the Sacred of Bunbun, the Sacred of Puak, and the Sacred of Batu Belah. In this article, researchers focused on the Myths behind the Sacred of Batu Belah, which still reflected the harmonious relationship between humans and nature. By using an ecocritic approach, the researcher answers the variable related with the relationship between man and nature behind the myth. The method used is a qualitative method with in-depth interviews and observation as data collection techniques. Using critical analysis techniques, the results of this study indicated that the ecocritic representation behind the Batu Belah myth is reflected from the existence prohibitions behind it. These prohibitions show how the Malay community is still able to maintain a harmonious relationship between humans and nature.